2020
DOI: 10.1371/journal.pone.0239484
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of choroidal thickness in prodromal Alzheimer’s disease defined by amyloid PET

Abstract: Objective To assess and compare the involvement of choroidal thickness (CT) in patients with mild cognitive impairment (MCI) and dementia due to Alzheimer's disease (AD) defined by amyloid PET and healthy controls (HC). Methods Sixty-three eyes from 34 AD patients [12 eyes (19.0%) with dementia and 51 eyes (80.9%) with MCI], positive to 11 C-labelled Pittsburgh Compound-B with positron emission tomography (11 C-PiB PET/CT), and the same number of sex-and age-paired HC were recruited. All participants underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…A decrease in choroidal thickness has been reported in patients with AD compared with healthy older subjects [15,33,34,[45][46][47][48][49]. These changes have also been observed in early stages of the disease [32], including in patients with preclinical and prodromal AD [49] and those with mild cognitive impairment (MCI) [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A decrease in choroidal thickness has been reported in patients with AD compared with healthy older subjects [15,33,34,[45][46][47][48][49]. These changes have also been observed in early stages of the disease [32], including in patients with preclinical and prodromal AD [49] and those with mild cognitive impairment (MCI) [41].…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in choroidal thickness has been reported in patients with AD compared with healthy older subjects [15,33,34,[45][46][47][48][49]. These changes have also been observed in early stages of the disease [32], including in patients with preclinical and prodromal AD [49] and those with mild cognitive impairment (MCI) [41]. Choroidal thinning may indicate abnormal choroidal blood supply associated with hypoperfusion or atrophic changes related to various pathological events, with cerebral Aβ accumulation being the main trigger [33].…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al (41) measured brain cortical thickness and Aβ deposition but did not find any relationship with retinal parameters. On the other hand, López-de-Eguileta et al (4) used PET to demonstrate macular and choroidal (10) thinning related to the positivity of PiB in patients with AD and MCI.…”
Section: Resultsmentioning
confidence: 99%
“…They associated these findings with increased vascularity in the stromal vascular layer. 107 Patients with MCI had also significantly thinner choroid compared to controls according to Bulut et al 108 Conversely, recently Eguileta et al 109 found no significant reduction in the CT. Another study analyzed several choroidal structural parameters, namely the subfoveal choroidal thickness (SFCT), the total choroidal area (TCA), the luminal area (LA) and the choroidal vascularity index (CVI), in patients with AD, MCI, and healthy subjects. They found a higher TCA and LA in the AD and MCI group, whereas CVI was lower in MCI.…”
Section: Choroidmentioning
confidence: 95%